Occupational therapy for persons with cognitive impairments. - Schnell-Inderst P; Conrads-Frank A; Stojkov I; Krenn C; Kofler LM; Siebert U (German medical science : GMS e-journal, 2023)
BACKGROUND: Damage to the central nervous system can occur in adulthood, for example, due to stroke, trauma, tumours, or chronic diseases. After damage to the central nervous system, cognitive impairments occur in addition to physical limitations. Occupational therapy is most often prescribed for neurological diagnoses, including stroke and traumatic brain injury. METHODS: The health technology assessment (HTA) report this HTA article is based on investigates the clinical effectiveness, cost-effectiveness, and patient-related, social and ethical aspects of occupational therapy for patients with cognitive impairments compared to no occupational therapy. In addition, the effects of different occupational therapy interventions with and without cognitive components were compared in an explorative overview. Patients with moderate or severe dementia are excluded from the assessment. Systematic overviews, that is, systematic reviews of systematic reviews, were conducted. RESULTS: For the evaluation of clinical effectiveness, a total of nine systematic reviews were included. No systematic review was identified for the assessment of costs or cost-effectiveness. Five systematic reviews were included for the assessment of patient and social aspects. For the assessment of clinical effectiveness compared with no occupational therapy, five systematic reviews comprising 20 randomised controlled trials with a total of 1,316 subjects reported small positive effects for the outcomes "global cognitive function" and "activities of daily living" as well as a non-quantified positive effect on the outcomes "health-related quality of life" and "behavioural control". No effect was found for individual components of cognition and measures of perception. The quality of the evidence for all outcomes is low due to a high risk of bias. In the supplementary presentations, no positive effects could be demonstrated on the basis of the available evidence. The quality of this evidence was not assessed. For the assessment of patient and social aspects, five systematic reviews on patients with a stroke or a traumatic brain injury - without specification regarding cognitive deficits or studies with their relatives - were included. It was reported that patients and family caregivers go through different phases of rehabilitation in which the discharge home is a decisive turning point. The discharge home represents a crucial breaking point. Regaining an active, self-determining role is a process that requires therapists to find the right level of support for patients and relatives. For the assessment of ethical aspects, nine documents were included. We identified ethical problem-solving models for occupational therapy and 16 ethical aspects in occupational therapy for cognitive deficits. The central theme of the analysis is the limited autonomy due to the consequences of the disease as well as the resulting tensions with those treating the patient. CONCLUSIONS: Based on this systematic overview, it can neither be proven nor excluded with certainty that occupational therapy for cognitive impairment is an effective therapy for adult patients with central nervous system injuries compared to no occupational therapy. There is a lack of randomised trials with sufficient sample size, well-defined interventions, and comparable concomitant therapies in the control groups, but there is also a lack of well-designed observational studies in routine care and health economic studies. The identified systematic reviews on patient and social aspects provide information on the needs of patients after stroke or traumatic brain injury and their relatives, but there is a lack of studies on this aspect in German-speaking countries. For the ethical assessment, in addition to the identified theoretical models for solving ethical conflicts in occupational therapy, more empirical studies on ethical aspects with patients with cognitive deficits and their relatives as well as occupational therapists are needed.